Treating hepatitis C virus in dialysis patients: How, when, and why?. Issue 2 (26th November 2018) - Pagan, Javier; Ladino, Marco; Roth, David
Abstract: The identification of hepatitis C virus (HCV) occurred in 1989, and soon thereafter, it was recognized that there was a higher prevalence of anti‐HCV seropositivity in patients with end‐stage renal disease (ESRD) when compared to the general population. Multiple extrahepatic manifestations have been associated with HCV infection in patients with ESRD; these include an increased prevalence and risk of cardiovascular complications, insulin resistance, diabetes mellitus, and lymphoproliferative disorders. Infection with HCV has also been associated with an increased relative risk of mortality in the ESRD patient when contrasted to those patients without infection. The availability of second‐generation direct‐acting antiviral agents has revolutionized the treatment of HCV in both the general population as well as those patients with advanced chronic kidney disease and receiving dialysis. These new treatment protocols are very well tolerated with limited side effects and manageable drug‐drug interactions while achieving remarkable sustained viral response rates. It is important that nephrologists become familiar with the differing strategies available for HCV‐infected ESRD patients so that the appropriate decision of when and who to treat can be made for each patient.